Different Effect of Donation Ionophoresis and Phonophoresis for Pain Reduction in Carpal Canal Syndrome - Sri Suwarni; Fendy Nugroho (Nur Science Institute, 2022)
The thenar pain and paresthesias experienced by people with CTS greatly interfere with their daily activities. Long-lasting repetitive strain injuries, thickening of the yellow ligament and pregnancy are suspected to be the cause. Objective: To determine the difference in effect of iontophoresis and phonophoresis in reducing pain in CTS cases. The research subjects were CTS patients who visited the physiotherapy center at UNS Hospital in Surakarta. Method: experimental research with two pre and post test design groups. 21 subjects aged 26 to 61 were randomly assigned to 2 groups, 10 were assigned to the iontophoresis group and 11 to the phonophoresis group. The cream used contains methyl salicylate. Pain assessment was performed before and after the intervention in both groups. Analysis: Test of normality of the VAS pain data before treatment of the two groups with the Shapiro Wilk test obtained p 0.05. Pre-test VAS homogeneity test in the two groups with the results of the Mann Whitney test obtained p 0.05. The pre and post difference test for each group used Wilcoxon's test with results for all groups showing p≤ 0.05. The difference test between the pre and post VAS differences using the Mann Whitney test was obtained p 0.05. Results: The difference between the pre and post VAS tests between the two groups showed that the two interventions did not show a different effect, but the pre and post VAS tests for each group showed significant results. Conclusion: The two interventions have the same effect on pain reduction in CTS cases.